GAMBARAN PENGETAHUAN REMAJA PUTRI TENTANG PREMENSTRUAL SYNDROME (PMS) DI DESA SEPILUK TAHUN 2022 - Tri Maharani (STIKES ADVAITA MEDIKA TABANAN, 2023)
Premenstrual syndrome is a collection of symptoms that arise just before menstruation that causes disruption to a person's work and lifestyle. Recorded in the area of ​​West Kalimantan shows that around 80-90% of women experience physical and psychological disorders before menstruation or also known as premenstrual syndrome. The disorder may be felt by women aged 12 to 50 years or at the beginning of puberty and ends until menopause. Using descriptive research techniques with a survey approach. With a simple random sampling technique. The instrument used is a questionnaire, with a sample of 42 respondents. Knowledge of young women about the notion of premenstrual syndrome have good knowledge (31 respondents or 74%), about the symptoms of premenstrual syndrome have less knowledge (32 respondents or 76%), about the impact of premenstrual syndrome have sufficient knowledge (22 respondents or 52%), about how to overcome premenstrual syndrome have less knowledge (25 respondents or 59%).